A new species of glyptodontine (Mammalia, Xenarthra, Glyptodontidae) from the Quaternary of the Eastern Cordillera, Bolivia: phylogeny and palaeobiogeography. (16th September 2020) - Cuadrelli, Francisco; Zurita, Alfredo E.; Toriño, Pablo; Miño-Boilini, Ángel R.; Perea, Daniel; Luna, Carlos A.; Gillette, David D.; Medina, Omar
Abstract : Xenarthrans constitute a relict clade of endemic South American placental mammals with a long evolutionary history starting, at least, in the early Eocene. Within Xenarthra, Glyptodontidae (late Eocene–earliest Holocene) was a conspicuous group of large-sized armoured herbivores. During the Pleistocene ( ca . 2.6–0.001 Ma) several genera (e.g. Panochthus and Glyptodon ) achieved a remarkable latitudinal distribution in South America, as members of one of the xenarthran groups that participated in the Great American Biotic Interchange. Knowledge of the evolutionary history of this clade in some areas remains poorly known, especially in the high elevation Andean and sub-Andean regions of South America. Here we describe a new species, Glyptodon jatunkhirkhi sp. nov., from several localities of the Eastern Cordillera in Bolivia ( ca . 2500–4100 m above sea level). From a phylogenetic viewpoint this new taxon appears as the sister group of the two lowland species recorded in southern South America ( Glyptodon munizi + G. reticulatus ), and this is congruent with the morphological differences observed between both clades, mainly with respect to the general morphology of the dorsal carapace and the skull. This new species expands the complex biogeographical scenario for Pleistocene glyptodonts and highlights the importance of Andean areas as key in understanding the evolutionary history of this clade. According to this revision, the diversity of Glyptodon is limited to G. munizi and G. reticulatus (two chronologically successive lowland species) plus this new species. The genera Panochthus ( P. hipsilis ) and Glyptodon seem to be the only Pleistocene glyptodonts to have been adapted to high elevation environments. http://zoobank.org/urn:lsid:zoobank.org:pub:7B5EFC11-626A-4BB5-8A00-DF657741698C